Advances in Automated Driving Systems - Arno Eichberger; Zsolt Szalay; Martin Fellendorf; Henry Liu (Energies, 2022)
Electrification, automation of vehicle control, digitalization and new mobility are the mega trends in automotive engineering and they are strongly connected to each other [...]